Asymmetric Transformations of α-Hydroxy Enamides Catalyzed by Chiral Brønsted Acids - Rajkumar, Subramani; Wang, Jiawen; Yang, Xiaoyu (Synlett, 2019)
2-Aminoallyl cations are reactive intermediates that undergo diverse reactions, such as cycloadditions, direct nucleophilic additions, Nazarov electrocyclizations, and rearrangements. We review recent development in asymmetric catalytic reactions (nucleophilic additions and Nazarov electrocyclizations) based on chiral counteranion-paired 2-aminoallyl cation intermediates generated through activation of α-hydroxy enamides in the presence of chiral Brønsted acid catalysts. With an understanding of their asymmetric catalysis modes and mechanisms, we expect more asymmetric catalytic reactions will be developed on the basis of this strategy in the near future.
Keywords: aminoallyl cations; hydroxy enamides; chiral anion catalysis; Brønsted acids; indole addition; Nazarov electrocyclization